PENGARUH MEDIA SOSIAL LINE WEBTOON TERHADAP MINAT MEMBACA KOMIK PADA MAHASISWA UNIVERSITAS RIAU - Destya Maya Putri; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The development of social media today accommodate a variety of works. Ideas in the form of photos, videos and writings and even potrait and comics including the types of works that can be found on various social media. Social media both content and characteristics of social media is quite diverse, most social media is a place to socialize, share opinions and chatting through chat but social media a little different is LINE Webtoon. LINE Webtoon is a digital comic reading app that is part of LINE's social media products. Comics on social media LINE Webtoon can be accessed for free and have many different genres and titles. The webtoon user segmentation is quite extensive, ranging from 14 years old to adults including among students. Researchers want to know the influence of social media LINE Webtoon to interest in reading comic students of Riau University. LINE Webtoon social researcher used by students of Riau University and students to respond in the form of interest in reading comics. The purpose of this study to determine the influence of social media LINE Webtoon to interest in reading comic students of Riau University.The method used is the method of quantitative explanation research, data collection techniques in this study using questionnaires. The number of samples in this study were 96 respondents. Sampling using Accidental Sampling. To find out how big the influence of these two variables, the researcher uses a simple linear analysis. For data processing questionnaire, done by using Program Statistic Product And Service Solution (SPSS) Windows version 17.The results of research on the influence of social media LINE Webtoon with indicators (Participation, Openness, Conversation, Community and Interconnected) to the interest in reading comics (the need for reading, reading-seeking, fun to read, interest in reading, continued) on the students of Riau University obtained regression coefficient value Y = 5.904 + 0.610 X with a significance level of 0.000 smaller than α = 0.05. This means that there is an influence of social media LINE Webtoon to interest in reading comics on students of the University of Riau for 49.7% and fall into the middle category of influence is. The percentage indicates that Social Media LINE Webtoon affects reading interest. thus H0 is rejected and Ha accepted.Keyword : Social Media, LINE Webtoon, Interest in reading comics